The Persistent Generalized Muscle Contraction in Siblings with Molybdenum Cofactor Deficiency Type A - Yoshimura, Ayumi; Kibe, Tetsuya; Hasegawa, Hiroshi; Ichida, Kimiyoshi; Koshimizu, Eriko; Miyatake, Satoko; Matsumoto, Naomichi; Yokochi, Kenji (Neuropediatrics, 2019)
Molybdenum cofactor deficiency (MoCD) is a rare autosomal recessive metabolic disease with severe neurological symptoms. Most disease-causing mutations are found in the MOCS1 gene, corresponding to MoCD type A (MoCD-A). There have been few reports describing the long-term detailed neurological features with MoCD-A because most patients do not survive childhood. We describe the clinical, radiologic, biochemical, and genetic data of two patients (female siblings aged 26 and 22 years) with MoCD-A. Both patients presented with feeding difficulties, neurological deterioration, and persistent generalized muscle contraction which can be easily confused with status dystonicus. Biochemical tests revealed low serum uric acid, elevated urinary sulfocysteine, and xanthine. Brain magnetic resonance imaging (MRI) revealed distinctive abnormalities in the bilateral caudate nucleus, putamen, globus pallidus, and cerebral white matter adjacent to the cortex. The thalamus was relatively unaffected. Genetic testing identified a novel homozygous variant in the MOCS1 gene (c.949C > T p.Arg317Cys). Biochemical results supported the hypothesis that this genetic variant is a pathological mutation. When there are symptoms of persistent generalized muscle contraction and characteristic MRI findings, MoCD should be considered as a differential diagnosis.
Keywords: molybdenum cofactor deficiency; MOCS1; status dystonicus; persistent generalized muscle contraction